Noise Emissions Mapping from Ampang Line LRT - Arbaan, A; Othman, M H; Tong, Y G; Ab Ghani, A R; Ambak, K; Borhan, M N; Abdul Sukor, N S (2023)
Train transportation is considered safe, sustainable, and climate-friendly mode of transportation. However, it may also lead to higher noise which may be annoying, disrupt sleep, and disturbance on residents who live nearby the train track. The aims of this study are to evaluate Light Rail Transit (LRT) noise level in urban area, at LRT Ampang Line by using grid lines method and to develop LRT noise mapping. The residential area that is located near the track was chosen in this study. The measurement of noise level for train passing-by was measured using B&K Type 2250 which was placed at 1.2 meter above the ground level. Noise measurement was carried out using 25 m x 25 m grid lines with short-term sampling method of 20 minutes of measurement for each point. The LRT noise level in the study areas at distance of 15 m from the centre of train tracks was found to be higher (77.04 dBA) than noise limit (65 dBA) guidelines from Department of Environment. The graph trendline of noise level was decreasing from 15m (30.64 dBA) to 115m (8.68 dBA) from the centre of the train tracks. These shows that the further the distance of the Sound Level Meter (SLM) placement, the lower the difference of the noise train pass-by and the background noise. The LRT noise mapping will be useful for the future LRT noise prediction